Understanding the currency manufacturing process - Gómez Nájera, Luis Daniel (2025)
This thesis evaluates the operational performance of the cash printing processes of the National Bank of Guatemala using the framework of the Five Performance Objectives of Operations Management: Quality, Speed, Dependability, Flexibility, and Cost. The study begins with a historical contextualization of operations management and the evolution of printed money, establishing the importance of cash within modern financial systems. Subsequently, a methodological model based on international standards applied by central banks is developed and implemented in the Guatemalan context through the use of fifteen operational variables. The evaluation revealed solid results in the objectives of Quality and Dependability, supported by strict security features and stable operational procedures. However, limitations were identified in Speed and Flexibility, particularly in production lead times, technological adaptation, and the capacity to adjust the money supply in response to unexpected variations. These gaps highlight the need to modernize key components of the operational process. This thesis contributes to the academic field by demonstrating that the Five Performance Objectives, commonly applied to industrial processes, can be effectively adapted to a specialized financial context such as banknote production. Additionally, the study provides practical recommendations aimed at improving operational performance, strengthening institutional resilience, and ensuring the long term efficiency of the cash management system in Guatemala.